Keandalan Metode Backup Data dalam Business Continuity Plan: Analisis Electronic Vaulting, Remote Journaling, dan Database Shadowing - Syifa Nurgaida Yutia; Zuki Pristiantoro Putro (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Data security and availability are crucial aspects of an organization's operational sustainability, particularly in addressing potential disruptions such as system failures, human errors, natural disasters, or cyberattacks. A Business Continuity Plan (BCP) is designed to ensure that critical business processes can continue operating despite incidents that threaten operations. One of the key elements of BCP is data backup strategies, which serve to maintain the integrity and availability of information within a system. This study explores the implementation of three primary data backup methods Electronic Vaulting, Remote Journaling, and Database Shadowing in a MariaDB database environment. The research employs an experimental approach, in which these three backup strategies are implemented within a MariaDB-based system. Electronic Vaulting is used for periodically backing up data to a secondary server to ensure data security in disaster recovery scenarios. Remote Journaling records transaction changes in near real-time, allowing data synchronization with a backup server without requiring full database storage at all times. Database Shadowing combines database replication and server fault tolerance mechanisms, ensuring that data is simultaneously updated across multiple locations. The implementation of these backup strategies is expected to enhance system resilience against disruptions and ensure the continuity of organizational operations in the event of data loss. This study provides insights for organizations in selecting and implementing data backup strategies that align with their Business Continuity Plan. Future research may explore the integration of encryption in data backups, additional security mechanisms such as multi-factor authentication, and the use of cloud backup services to enhance system flexibility and resilience.